Temperature Effect on Mohr–Coulomb’s Effective Strength Parameters of Paste Backfill - Hasan, Alsidqi; Ting, Wee Kiet (Frontiers in Materials, 2022)
In-stope paste backfill monitoring at different mine sites showed anomalous increase in total stress during rest period. A recent laboratory-model experiment has proved that the total stress anomaly was due to the temperature increase within the backfill. This paper extends the understanding whether the effective stress is also affected by such temperature increase. The effects are explained through evaluating the effective internal and interfacial friction angles under different temperature conditions. A series of modified direct shear tests were performed on saturated samples at controlled temperature of 25 °C, 50 °C, and 70 °C. The samples consist of cemented paste backfill and uncemented paste backfill. The results show that the effective internal and the interfacial friction angles increase as the temperature increase depending on the type of material and the shearing condition. The findings serve as a reference for engineers and academics in explaining the stress anomaly and to better understand the shear behavior of paste backfill under different temperature condition for mine stope backfill design.